Identifikasi Jenis Jamur Basidiomycetes Di Kecamatan Sosa Kota Padang Lawas Desa Harang Julu - Apradina Mawarni; Fitri Amalia; Fadlya Purnama Hasibuan; Jelita Purnama Sari; Syarifah Widya Ulfa (Peneliti.net, 2023)
Basidiomycota mushroom is a type of fungus that can be seen directly by the eye, this fungus acts as a counterweight to natural ecosystems. The village area of ​​Harang Julu is an ecosystem with several types of habitats that support mushroom growth. This area has a diversity of mushrooms that have not been widely explored. The purpose of this study was to determine the diversity of species and the potential for macroscopic fungi in the Harang Julu village area. The study was conducted in lowland primary forest habitat types from April to May 2023. Methods used is an exploratory survey. The number of macroscopic fungal species found are 11 species of mushrooms Pleurotus spp, Ganoderma applanatum, Schizophyllum commune, Coprinopsis atramentaria, Phallus impudicus, Ganoderma lucidum Karst, Daedaleopsis eff, Confragosa, Lepiota sp, Schyzopylum commune, Coprinusmicaceus and p. sanguineus Each location has a different type in common. Index diversity is included in the low category.The type of mushroom that has the highest role in each location is Ganoderma sp.